2022
DOI: 10.1007/s11096-022-01448-x
|View full text |Cite
|
Sign up to set email alerts
|

Views, experiences and contributory factors related to medication errors associated with direct oral anticoagulants: a qualitative study with physicians and nurses

Abstract: Background Direct oral anticoagulants (DOACs) have become preferable for the management of thromboembolic events. Recent publications have however identified high volume of medication errors related to DOACs. There is limited literature on why and how such errors occur or happen in clinical practice. Aim This study aimed to explore views, experiences, contributory factors related to DOACs medication errors from the perspectives of healthcare profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Moreover, our study participants revealed that the clinical pharmacist role was vital to improving patient care, especially for patients with chronic disease, comorbidities and receiving polypharmacy. Pharmacists' involvement in care with other HCPs was also emphasised by physicians and nurses in our previous study [ 12 ]. Physicians' views highlighted the pivotal role of multidisciplinary teamwork in preventing medication errors [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our study participants revealed that the clinical pharmacist role was vital to improving patient care, especially for patients with chronic disease, comorbidities and receiving polypharmacy. Pharmacists' involvement in care with other HCPs was also emphasised by physicians and nurses in our previous study [ 12 ]. Physicians' views highlighted the pivotal role of multidisciplinary teamwork in preventing medication errors [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reason's Accident Causation model distinguishes active failures, such as human mistakes and violations, from latent failures associated with system-related factors, such as lack of resources [ 10 ]. A previous study identified that lack of adequate knowledge and training of physicians and nurses about DOAC, lack of confidence in prescribing and administration and lack of access to clinical guidelines as key factors related to medication errors with DOAC [ 12 ]. However, pharmacists' perspectives on DOAC related errors and effective strategies to mitigate the contributory factors have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, DOACs were most commonly associated with severe harm, including 25% of all fatal errors, making it the most harmful therapeutic area in the reported incidents [ 5 ]. Other studies have shown that medication errors associated with DOAC’s resulted in high mortality and morbidity and cause a long stay in hospital [ 6 , 7 ]. A retrospective study by Piazza et al identified that the medication errors were the common root cause in 40% of anticoagulation-related adverse events [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Direct oral anticoagulants (DOACs) have been preferred over warfarin by clinical guidelines, due to their superior safety profile. They also provide practical advantages such as no need for prothrombin time (PT) or international normalized ratio (INR) monitoring, and fewer drug interactions, thus resulting in an increasing utilisation in clinical practice [ 16 ]. However, despite these advantages, there is still an alarming rate of prescribing errors, where almost 1 in 5 patients on DOACs have experienced a prescribing error such as under or overdosing, duplication of therapy and contraindications.…”
Section: Introductionmentioning
confidence: 99%